Produção e caracterização de eletrodos de Ti-Pt/PbO2 dopados e seu uso no tratamento eletroquímico de efluentes simulados - Andrade, Leonardo Santos (2006)
Ti-Pt/PbO2 electrodes were obtained by electrodeposition of PbO2 films at 65 °C and with different dopant(s) (Fe, Co, F, Fe and F, Co and F) contents in the oxide matrix, which were controlled under pre-established and optimized conditions (current densities as well as concentrations of the dopant ions in the electrodeposition baths). Tafel curves in 0.5 mol L-1 H2SO4 showed that the higher the dopant content in the films, the higher was the electrocatalytic activity towards the oxygen evolution reaction (OER), whose mechanism, in a general way, was not changed. The increased electrocatalytic activity was considered as resulting from oxygen defects in the crystalline structure of the oxides, due to dopants action and also morphologic effects. The structural characterization of the films by X-ray diffractometry showed that the structure of the films was always the same, i.e. β- PbO2. The electrochemical performance of pure Ti-Pt/β-PbO2 electrodes, or doped with Fe, Co and F (together or separately), in the oxidation of simulated wastewaters containing the reactive blue 19 dye (RB 19) or phenol, using filter-press reactors, was carried out and then compared with that of a boron-doped diamond electrode (Nb/BDD). For the electrooxidation of the dye ([RB 19]o = 25 ppm, Q = 2.4 L h-1, i = 50 mA cm-2, V = 0.1 L, θ = 25 oC and A = 5 cm2), the results showed that: a) the performances of the electrodes in the dye decolorization were quite similar, achieving 100% decolorization, but in some cases 90% decolorization was achieved by applying only ~0.3 A h L-1 (8 min); b) the reduction of the wastewater organic load, monitored by its total organic carbon content (TOC), was greater for the 1 mM Ti- Pt/β-PbO2-Fe,F electrode (obtained from an electrodeposition bath containing 1 mM Fe3+), which presented a COT reduction of 95% after 2 h of electrolysis, while for the pure β-PbO2 and Nb/BDD electrodes the reductions were 84% and 82%, respectively. In the case of phenol electrooxidation in the semi-pilot scale ([phenol]o = 1000 ppm, Q ~ 120 L h-1, i = 100 mA cm-2, V = 1 L, θ = 40 ºC and A = 63 cm2), the 1mM Ti-Pt/β-PbO2-Co,F and Ti-Pt/β-PbO2 electrodes were the most efficient ones, attaining COD (chemical oxygen demand) reductions of approximately 75% and 63% and COT reductions of approximately 51% and 43%, respectively.